Strategi Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di SDN 066043 Kecamatan Medan Helvetia - Purba, Juni Sinarinta; Zasneda, Sabriani Suci; Syahfitri, Ragil; Ginting, Edelwayss Br (3031-8572, 2023)
Improving learning quality in schools is greatly influenced by principal leadership. This research aims to identify principal strategies in planning, implementing, and supervising learning quality improvement at SDN 066043 Medan Helvetia District. This research used descriptive qualitative method with observation, interviews, and documentation as data collection techniques. Research subjects included committee members, principal, teachers, and students. Results showed principal strategies in quality planning involved all stakeholders, conducted at beginning of academic year and semester, implemented strict student selection, and optimized available resources. Implementation strategies included empowering teachers through training and seminars while providing broader authority in managing learning. Supervision was conducted weekly and monthly using individual and group supervision techniques. Obstacles included incomplete facilities and infrastructure, lack of donors, absence of sports field, and insufficient teacher discipline. Conclusion: The principal has implemented comprehensive quality improvement strategies involving all school stakeholders, although not yet optimal due to various constraints requiring solutions through collaborative efforts with all parties.